TECHNOLOGY DEVELOPMENT SOFTWARE FOR ANALYSIS OF INFLUENCE OF THICKNESS OUTSIDE OF THE CYLINDRICAL HINGE ON ITS STRESS-STRAIN STATE - Лютак, Ігор Зіновійович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The presented method of finite-element analysis based on ANSYS Workbench researches the stress-strain state in a cylindrical hinge limited size. Demonstrated the presence of the influence of geometrical dimensions of cylindrical hinge parts on its mode of deformation. An approach to building software that must be integrated into the process of development of models in this system is presented. The algorithm of the software is demonstrated. Established inability to use the theoretical method Hertz-Belyaev to determine the stress-strain state of conjugacy cylindrical hinge in large quantities relative load.